Heinrich von Kleist the Biography - Blamberger, Günter 1951- (Schöningh and Fink Literature and Culture Studies E-Books, Collection 2021, ISBN: 9783657100255, 2021)
Kleist has fascinated readers like no other German writer. How did a one-time soldier with an unremarkable literary education become one of the greatest innovators of German literature? What allows for the tragedy of his life? In what ways does his work speak to us today? In his great biography Günter Blamberger gives us a new Kleist: Unlike conventional approaches, he does not try to understand Kleist's life from the perspective of its end-from the perspective of his suicide as the final catastrophe of a life in permanent crisis. Rather, he remains at eye-level with Kleist's present, narrating from the perspective of Kleist's experience-in the moment with him-capturing the unsettling or the astonishing in each phase of his life, the explosive nature of each one of his risky experiments in living and writing. The result is an indispensable work of German literary history-a vivid, captivating biography of one of the greatest literary geniuses of all time